"I Was Becoming Increasingly Uneasy About the Profession and What Was Being Asked of Me": Preserving Integrity in Teaching. Issue 5 (December 2013) - Santoro, Doris A.
Abstract: This article offers a model of the relationship between three dimensions of integrity in teaching: personal integrity, professional integrity, and the integrity of teaching and illustrates the model through interview excerpts from 13 experienced former teachers. I argue that experienced teachers' decisions to leave work they love can be understood not only as attempts to preserve their personal integrity, but also to preserve the integrity of teaching by withdrawing their corroded professional integrity. Only by looking at all three dimensions of integrity can the actions of teaching's conscientious objectors be viewed as moral commentary on a moral enterprise rather than the private and personal laments of disgruntled individuals. When the role of teacher serves as a significant source of moral identity, protecting the integrity of teaching is deeply connected to protecting one's personal integrity. Diminishment in what counts as teaching results in a diminishment of the self. Rather than viewing teachers who leave for matters of conscience as lacking sufficient commitment or ceasing to care about their work, this analysis views their choices as reflecting deep investment in preserving the practice of teaching.